Applying Contingent Valuation Method for Economic Valuation of Awqaf Wealth Management in Welfare Changes of Muslim Households in - Sarabdeen Masahina; A.C. Muhammadu Kijas (Institute for Research and Community Empowerment (LPPM TAZKIA), 2012)
Objective- The main objective of this study is to estimate the Willingness to Pay of the Muslim households to contribute cash waqf as a strategy towards wealth management in Sri Lanka. Waqf is holding or confinement which is emphasised in Islam as ibadah as it can distribute the wealth among the Muslim society and would help to develop the Islamic vision of brotherhood.Method- Contingent valuation method is used to estimate the Willingness to Pay of Muslim households to improve socio-economic status of the low income people through waqf wealth management in Sri Lanka. This study is developed based on Random Utility Theory.Result- This paper identifies the appropriate methods to estimate the willingness to pay of Muslim households in Sri Lanka for waqf (awqaf is plural) institutions. Such evaluations are crucial for the Islamic financial system to function effectively in order to achieve the dignified objectives of socio-economic justice through proper distribution of wealth.Conclusion-This paper presents a conceptual model of waqf institutions which would be useful for further empirical research in this area. The findings are not only appropriate and applicable to Sri Lanka but also to other Muslim and non-Muslim countries. This is a unique contribution to the Islamic economic literature. The knowledge obtained from this study hopes to propose cash waqf to manage the wealth in order to improve the socio-economic status of low income people in Sri Lanka.Tujuan - Tujuan utama dari penelitian ini adalah untuk memperkirakan Kemauan Membayar rumah tangga Muslim untuk berkontribusi wakaf tunai sebagai strategi menuju pengelolaan kekayaan di Sri Lanka. Wakaf secara bahasa menahan (harta) yang ditekankan dalam Islam sebagai ibadah karena dapat mendistribusikan kekayaan di antara masyarakat Muslim dan akan membantu untuk mengembangkan visi Islam yaitu persaudaraan.Metode - Metode penilaian Kontingensi digunakan untuk memperkirakan Kesediaan membayar rumah tangga Muslim dalam meningkatkan status sosial - ekonomi masyarakat berpenghasilan rendah melalui pengelolaan kekayaan wakaf di Sri Lanka. Penelitian ini dikembangkan berdasarkan Teori Utilitas Acak.Hasil - Paper ini mengidentifikasi metode yang tepat untuk memperkirakan kemauan membayar rumah tangga Muslim di Sri Lanka untuk wakaf lembaga. Evaluasi tersebut sangat penting untuksistem keuangan Islam yang berfungsi secara efektif dalam rangka mencapai tujuan yang bermartabat keadilan sosial - ekonomi melalui distribusi kekayaan yang tepat.Kesimpulan - Paper ini menyajikan model konseptual lembaga wakaf yang akan berguna untuk penelitian empiris lebih lanjut di daerah ini. Temuan ini tidak hanya tepat dan berlaku untuk Sri Lanka, tetapi juga ke negara-negara Muslim dan non -Muslim lainnya. Ini adalah kontribusi yang unik untuk literatur ekonomi Islam. Pengetahuan yang diperoleh dari studi ini adalah mengharapkan agar wakaf tunai diusulkan untuk mengelola kekayaan dalam rangka meningkatkan status sosial - ekonomi masyarakat berpenghasilan rendah di Sri Lanka.Keywords: Awqaf, Contingent Valuation Method, Utility Theory, Willingness to Pay, Welfare Changes